1993
DOI: 10.1002/app.1993.070480104
|View full text |Cite
|
Sign up to set email alerts
|

A generalized model to predict the viscosity of solutions with suspended particles. I

Abstract: SYNOPSISSeveral suspension equations available in the literature have been found to have a common derivative form. This common derivative was found to be equivalent to a ratio of the intrinsic viscosity, [ q ] , and a quantity, VInt, defined as the "relative suspension interaction volume" available for particle flow. V,,, was, in general, found to be a relatively simple function of the suspension particle volume fraction, cp, the maximum particle packing fraction, cpn, and a new variable, 6, defined as the pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
120
0

Year Published

1993
1993
2018
2018

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 103 publications
(122 citation statements)
references
References 19 publications
2
120
0
Order By: Relevance
“…In 1962, Rutgers 30 listed 96 equations and classified them into various categories such as theoretical, semi-empirical, empirical, Einsteinian, logarithmic, and polynomial. Sudduth 31 then showed that many of these equations differ only in the degree to which they account for intermolecular interactions.…”
Section: Macroscopic and Microscopic Descriptions Of Solution Viscositymentioning
confidence: 99%
“…In 1962, Rutgers 30 listed 96 equations and classified them into various categories such as theoretical, semi-empirical, empirical, Einsteinian, logarithmic, and polynomial. Sudduth 31 then showed that many of these equations differ only in the degree to which they account for intermolecular interactions.…”
Section: Macroscopic and Microscopic Descriptions Of Solution Viscositymentioning
confidence: 99%
“…It is known that suspensions composed of binary sized spherical particles yield a maximum packing fraction approximately larger than the random close packing for a homogenous suspension. 5,[23][24][25] However, albumin is a prolate ellipsoid that has been shown to inuence the maximum packing fraction. It has been predicted that for globular protein solutions up to approximately 250 mg mL À1 with the protein having a 5 : 1 aspect ratio, the increase of jamming limit would not be signicant.…”
mentioning
confidence: 99%
“…The models proposed by Farris [25] and Sudduth [26][27][28] are starting points for more recent equations for predicting the viscosity in multimodal systems. However, Farris' model does not account for interactions between the particles, and has been shown to fail in the case of typical colloidal dispersions.…”
Section: Viscosity Of Bimodal Laticesmentioning
confidence: 99%